Implementation of School Well-Being Concept in Islamic Religious Education Learning at Madrasah Ibtidaiyah - Kurnaengsih, Kurnaengsih; Sumarna, Cecep; Nurhayati, Eti; Rosidin, Didin Nurul (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study focuses on the implementation of the school well-being concept in Islamic religious education learning at Madrasah Ibtidaiyah Islamic Center Indramayu. The background of this study is the importance of creating a school environment that supports students' physical, psychological, and social well-being as part of efforts to improve the quality of education, especially in Islamic religious education learning. This study aims to answer five problem formulations: (1) Islamic religious education teachers' understanding of the concept of school well-being, (2) the application of the concept in Islamic religious education learning, (3) teacher and student responses to its application, (4) obstacles faced in implementation, and (5) the impact of implementation on students' Islamic character. This study uses a descriptive qualitative method with a case study approach, relying on data from semi-structured interviews, in-depth observations, and document studies. The results of the study indicate that teachers' understanding of the concept of school well-being is quite good, and the application of this concept is carried out through the integration of physical and psychological aspects in the learning environment, as well as the application of learning methods that involve students' emotional and social aspects. The use of educational technology is also part of this application. Teacher responses are very positive and enthusiastic, while students feel comfortable and show good responses to the application of this concept. However, there are several obstacles, such as the need to improve teacher understanding and readiness, limited resources and facilities, and support from family and the social environment. Cultural challenges and local values are also obstacles. The impact of the implementation of school well-being is very significant in the formation of Islamic character of students at the Islamic Center Indramayu Elementary School